2022
DOI: 10.1016/j.cjtee.2021.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Meniscus repair with simultaneous anterior cruciate ligament reconstruction: Clinical outcomes, failure rates and subsequent processing

Abstract: Purpose To retrospectively analyze the clinical outcomes of meniscus repair with simultaneous anterior cruciate ligament (ACL) reconstruction and explore the causes of failure of meniscus repair. Methods From May 2013 to July 2018, the clinical data of 165 patients who were treated with meniscus surgery and simultaneous ACL reconstruction, including 69 cases of meniscus repair (repair group) and 96 cases of partial meniscectomy (partial meniscectomy group) were retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
5
1
Order By: Relevance
“…While some subjective knee scores may be slower to recover after ACLR with LM repair compared to isolated ACLR,[18] numerous studies have shown the long term bene t of repairing meniscal lesions in the setting of ACLR, resulting in improved quality of life and decreased risk of osteoarthritis development. [29,[32][33][34] Yet, in this study, mean KOOS Symptoms scores were signi cantly lower for the ACLR + LM repair group compared to isolated ACLR and ACLR + LM injury left in situ groups. It is possible that the nature of non-surgically treated LM tears in this study was different compared to surgically treated LM injuries.…”
Section: Discussioncontrasting
confidence: 51%
“…While some subjective knee scores may be slower to recover after ACLR with LM repair compared to isolated ACLR,[18] numerous studies have shown the long term bene t of repairing meniscal lesions in the setting of ACLR, resulting in improved quality of life and decreased risk of osteoarthritis development. [29,[32][33][34] Yet, in this study, mean KOOS Symptoms scores were signi cantly lower for the ACLR + LM repair group compared to isolated ACLR and ACLR + LM injury left in situ groups. It is possible that the nature of non-surgically treated LM tears in this study was different compared to surgically treated LM injuries.…”
Section: Discussioncontrasting
confidence: 51%
“…This surgical treatment is commonly known as “operation”. The purpose is to treat or diagnose diseases to improve the body’s function and shape, such as removing diseased tissues ( 1 , 2 ), repairing injuries ( 3 , 4 ), and organ transplantation ( 5 , 6 ). Early surgery is limited to cutting and suturing on the body surface by simple manual methods such as abscess drainage, tumor resection, and trauma suturing.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been well established that meniscectomy during ACLR increases the chances of OA in patients; therefore, menisci preservation through repair has garnered increased interest among surgeons [ 5 ]. There are various techniques to repair menisci that have been studied and described like open and arthroscopic procedures, outside-in sutures, inside-out sutures, and all-inside sutures.…”
Section: Introductionmentioning
confidence: 99%
“…There have been studies that demonstrate good short- and medium-term results after these suturing procedures with various factors influencing the outcome of menisci repair (MR) and ACLR being one of them [ 6 ]. The success rate of MR was reported between 75% and 92% [ 5 ]. Due to the multitude of factors involved, there have been higher reoperation rates in patients who undergo meniscal repair [ 4 ].…”
Section: Introductionmentioning
confidence: 99%